2020
DOI: 10.1111/aogs.13956
|View full text |Cite
|
Sign up to set email alerts
|

Association between utilization and quality of antenatal care with stillbirths in four tertiary hospitals in a low‐income urban setting

Abstract: Introduction About 2.6 million stillbirths per year occur globally with 98% occurring in low‐ and middle‐income countries including Kenya, where an estimated 35 000 stillbirths occur annually. Most studies have focused on the direct causes of stillbirth. The aim of this study was to determine the association between antenatal care utilization and quality with stillbirth in a Kenyan set up. This information is key when planning strategies to reduce the stillbirth burden. Material and methods This was a case‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The study also revealed that as the number of ANC visits increases the risk of having an unknown time of stillbirth decreases. The finding was concurrent with previous studies conducted in Ethiopia [ 67 , 68 ], Kenya [ 69 ], and Nepal [ 40 ]. The plausible explanation might be related to the frequent ANC visits’ ability in identifying potential risk factors that contribute to stillbirth [ 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…The study also revealed that as the number of ANC visits increases the risk of having an unknown time of stillbirth decreases. The finding was concurrent with previous studies conducted in Ethiopia [ 67 , 68 ], Kenya [ 69 ], and Nepal [ 40 ]. The plausible explanation might be related to the frequent ANC visits’ ability in identifying potential risk factors that contribute to stillbirth [ 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…The inadequacy of and inequity in quality of antenatal care (ANC) services is increasingly receiving attention. [1][2][3][4][5][6][7] The key elements of ANC services captured under the facility surveys also indicate inadequate quality of care provision. 8 Concerns about the quality of ANC services have also been reported from India, primarily based on the retrospective data collected under the National Family Health Survey.…”
Section: Introductionmentioning
confidence: 99%
“…The inadequacy of and inequity in quality of antenatal care (ANC) services is increasingly receiving attention 1–7. The key elements of ANC services captured under the facility surveys also indicate inadequate quality of care provision 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, primary prevention is considered the cornerstone in preventing the spread of the disease [34][35][36]. This would describe the much higher prevalence of deaths from HIV/AIDS in developing countries compared to developed countries and even the higher deaths in the developed countries among poor people who have limited aces to health care facilities [37][38][39][40][41][42]. This fact is evident in maps 1 and 2 quoted from the WHO website 2017, especially compared to the extreme poverty presented earlier (Figure 3), where Africa carries the primary disease burden and deaths from the disease [43].…”
Section: Hiv/aidsmentioning
confidence: 99%